The Effectiveness of Using YouTube Video in Teaching Writing Ability of Procedural Text at MTS Al Jam’iyatul Washliyah Gedung Johor - Safitri, Lela; Sirait, Dahlia; Zulfitri (JURNAL ILMU PENDIDIKAN, 2024)
The aims of this study was to find out the significance effect of YouTube video in teaching writing ability of procedural text at MTS Al Jam’iyatul Washliyah Gedung Johor. The research design used in this study is an experimental design with a quantitative approach. The subject of the research was eighth grade of MTS Al Jam’iyatul Washliyah Gedung Johor which consisted of 50 students, there are class VIII-B as the experimental group and VIII-C as the control group. This research employed a test (pre-test and post-test) as an instrument and also observation and documentation as a compliment. They were organization ideas, developed ideas, grammar, vocabulary, and mechanics. After analyzing the texts written by the student, the researcher categorizes them into six categories, namely excellent, very good good, fair, enough, and need guidance. To analyzed data, the researcher used statistically and SPSS. The Mean Score and Improvement of The Students’ Writing Ability with YouTube Video 87.50% and without YouTube Video 68.75%. Students who taught by using YouTube video got higher score than students who taught without using YouTube Video. The results of calculations using the t test show that the t-test results from SPSS reveal a sig (2-tailed) of (0.01 < 0,05). There was significant effect of using YouTube Video for students, especially in english writing skills. The result of data analysis showed that by using YouTube video as media improved the students‘ ability in writing skill, stimulated the students to be more active, got interest, and motivation in joining the class.